Rural High North : A High Rate of Fatal Injury and Prehospital Death - Bakke, Håkon Kvåle; Wisborg, Torben (World Journal of Surgery, 2011)
Finnmark County is the northernmost county in Norway. For several decades, the rate of mortality after injury in this sparsely inhabited region has remained above the national average. Following documentation of this discrepancy for the period 1991–1995, improvements to the trauma system were implemented. The present study aims to assess whether trauma-related mortality rates have subsequently improved. All injury-associated fatalities in Finnmark from 1995–2004 were identified retrospectively from the National Registry of Death and reviewed. Low-energy trauma in elderly individuals and poisonings were excluded. A total of 453 cases of trauma-related death occurred during the study period, and 327 of those met the inclusion criteria. Information was retrievable for 266 cases. The majority of deaths (86%) occurred in the prehospital phase. The main causes of death were suicide (33%) and road traffic accidents (21%). Drowning and snowmobile injuries accounted for an unexpectedly high proportion (12 and 8%, respectively). The time of death did not show trimodal distribution. Compared to the previous study period, there was a significant overall decline in injury-related mortality, yet there was no change in place of death, mechanism of injury, or time from injury until death. Changes in injury-related mortality cannot be linked to improvements in the trauma system. There was no change in the epidemiological patterns of injury. The high rate of on-scene mortality indicates that any major improvement in the number of injury-related deaths lies in targeted prevention.